2010
DOI: 10.1111/j.1365-2362.2010.02290.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of small intestinal mucosal injuries as a result of NSAID administration

Abstract: The impact of short-term NSAID medication on the small intestine differed according to intestinal site, with most denuded areas identified in the proximal part and all ulcers in the distal part.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 29 publications
3
73
0
8
Order By: Relevance
“…Fortunately, the animal models of NSAID enteropathy are very good, reproducible and simple, and can serve as useful tools for gaining a better understanding of the pathogenesis of this disorder and for testing potential therapeutic/preventative agents. Administration of NSAIDs to rats, for example, results in ulceration predominantly in the distal jejunum and ileum [52] , the same regions where ulcers are concentrated humans [53,54] . While there will undoubtedly be some differences between rodent models and humans, the existing data suggest that the animal models will be predictive in terms of treatment and prevention strategies.…”
Section: Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Fortunately, the animal models of NSAID enteropathy are very good, reproducible and simple, and can serve as useful tools for gaining a better understanding of the pathogenesis of this disorder and for testing potential therapeutic/preventative agents. Administration of NSAIDs to rats, for example, results in ulceration predominantly in the distal jejunum and ileum [52] , the same regions where ulcers are concentrated humans [53,54] . While there will undoubtedly be some differences between rodent models and humans, the existing data suggest that the animal models will be predictive in terms of treatment and prevention strategies.…”
Section: Pathogenesismentioning
confidence: 99%
“…On the other hand, this mechanism does not explain the localization of ulcers in the jejunum and ileum in animal models and in humans. In their endoscopic study of diclofenac-induced small intestinal injury, Fujimori et al [54] observed denuded regions throughout the small intestine (perhaps indicative of a topical erosive effect), but ulcers were concentrated in the distal jejunum and ileum.…”
Section: Mitochondrial Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Most of previous studies focused on pharmacoeconomic analysis regarding upper GI toxicities of NSAID uses. However, recent reports showed that a very high incidence of lower GI damage has been reported in young, healthy, human subjects taking both a non-selective NSAID and a PPI, indicating that the PPI conferred little protection to lower GI tracts, which are major sites of NSAID-induced bleeding and perforation [30][31][32]. And several studies showed that COX-2 selective inhibitor could be a better choice to reduce mucosal lesions of the small bowel compared with non-selective NSAID with PPI [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Videoendoszkópos vizsgálatok igazolták, hogy az NSAID-szedők 75%-ában alakul ki nyálkahártya-sérülés a distalis gastrointestinalis traktusban, amely a vékonybél proximalis szakaszán nyálkahártya-károsodással, az ettől distalisabb szakaszon többnyire fekélyképződéssel jellemezhető [121]. Ezek -szemben a felső szakaszon kialakult szövődményekkel -nem előzhetők meg protonpumpagátlók adásával, mivel a savas pH kialakulásukban nem játszik szerepet, sőt akár kedvezőtlen hatásúak is lehetnek dysbiosis kialakításával [122].…”
Section: Az Nsaid-ok Az Alsó Gastrointestinalis Traktusban Kialakuló unclassified